The reverse gender wage gap in Bangladesh: Demystifying the counterintuitive - Rahman, Mustafizur; Al-Hasan, Md. (Springer, 2022)
There is a gender wage gap (men earning more than women) in labour market of most countries, to varying degrees, is widely recognised in relevant literature. In this backdrop, the findings of the ILO study (ILO 2018), based on an analysis of cross-country data, showing Bangladesh as an outlier in this regard, calls for an explanation and indepth investigation. Based on Bangladesh labour force data, the ILO report found factor-weighted hourly wage in Bangladesh to be 5.0% more for women compared to that of men. This counter-intuitive presence of reverse gender wage gap is a departure from results derived for all other countries in the sample of 60 countries. The study examines why the ILO results are what they are, what are the reasons that have informed the ILO findings and whether a different (improved) methodology would give other results. The study undertakes a re-estimation of gender wage gap in Bangladesh by changing the specifications in the ILO study, by deploying human capital, wage discrimination and segmented labour market theories and quantile regression. The study finds that under full specification men are found to earn more than women in the Bangladesh labour market, albeit not to a significant extent—the wage gap was found to be in the range of between 2.0 and 4.0%. While the study does not find strong embedded discrimination against women, it does find sectoral segmentation, and presence of glass ceiling in the Bangladesh labour market.